Persepsi Masyarakat Batak Toba terhadap Status Perempuan Lajang di Dusun Lumban Ratus Desa Pansur Napitu Kecamatan Siatas Barita Kabupaten Tapanuli Utara - Maria D. Panggabean; Elvri Teresia Simbolon; Roida Lumban Tobing; Jupalman Welly Simbolon; Masniar H Sitorus (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to find out and describe the Toba Batak Community's Perception of the Single Status of Women in Lumban Ratus Hamlet, Pansur Napitu Village, Siatas Barita District, North Tapanuli Regency. This research uses a qualitative research method using an interpretative descriptive qualitative approach method through participant observation and in-depth interviews. Primary data was obtained by researchers directly from data sources, namely village officials, community members and women who were still single in Lumban Ratus Hamlet. Secondary data is supporting data obtained by researchers from interviews, observations and documentation. Meanwhile, the data analysis techniques used are data reduction, data presentation, Spradley model analysis and drawing conclusions. The results of this research show that 1). The Toba Batak community's perception of single women in Lumban Ratus hamlet, Siatas Barita District, North Tapanuli Regency considers that it is not good for a woman to live alone, the community considers that unmarried women are called spinsters, unsold and too picky. One of the reasons why single women feel they haven't found the right soul mate. Society believes that not finding the right soul mate is not an excuse for single women if there is no interest in marriage and society also believes that the reason why women are single is also due to the influence of negative thoughts which influence the mindset of women who feel traumatized by other people's lives and their personal lives. 2). Various factors influence the perception of the Toba Batak community in Lumban Ratus hamlet towards single women in Pansur Napitu village, Siatas Barita sub-district, North Tapanuli Regency, including perpetrators of perception, being targets and objects as well as the influence of the situation.